Sharing Stories: Reflections of Professors’ Literacy Identities and Beliefs - Christy M. Howard; Ran Hu; Johna Faulconer (Networks: An Online Journal for Teacher Research, 2020)
Teacher identities and beliefs influence instructional practices. In order to explore this process, this self-study was conducted by three literacy professors from different ethnic backgrounds including one African-American professor, one Chinese national professor and one White professor. The purpose of this study was to examine how professors' literacy identities are shaped and how sharing these identities, experiences and beliefs in meaningful professional dialogues influences instructional practice. We examined the role of our identities and beliefs on our instructional practices using multiple forms of qualitative data such as journal entries, digital stories, and critical group discussions. Despite the range of differences among participants, we also shared commonalities in our identities and experiences. Findings from the study reveal that our literacy stories shaped our identities, our identities and beliefs shaped our instruction, and our reflective process shaped change in our practices. Through this process we were able to adjust our instruction in order to meet the diverse needs of our students. This reflective process influenced and improved our instructional decisions.
Keywords: literacy; identity; beliefs; instruction